×
Language:
H y p e r b o lic F u n c t io n s ( E u le r )
e
x
+e
\u2212x
2
w ill b e c a lle d t h e H y p e r b o lic C o s in e ,c o s hx .
e
x
\u2212e
\u2212x
2
w ill b e c a lle d t h e H y p e r b o lic S in e ,
sin hx .
Sym m etrically,sin h andc o s h are derivatives,
and also antiderivatives, of each other.
T h e H y p e r b o lic T a n g e n t is t h e ir q u o t ie n t :
t a n hx\u2261
sin hx
c o s hx
=
e
x
\u2212e
\u2212x
ex
+e\u2212x
.
W e also have
s e c hx\u2261
1
c o s hx
,
c o s e c hx\u2261
1
sin hx
,
c o t a n hx\u2261
c o s hx
sin hx
.
e
x
+e
\u2212x
2
+
e
x
\u2212e
\u2212x
2
\ue002
e
x
+e
\u2212x
2
\ue003
2
\u2212
\ue002
e
x
\u2212e
\u2212x
2
\ue003
2
=
\ue002
c o s h2x\u2212 s in h2x =
1.
P r o o f.
\ue003
\ue002
e
x
+e
\u2212x
2
\u2212
e
x
\u2212e
\u2212x
2
\ue003
=
\ue002
2
e
x
2
\ue003
\ue002
2
e
\u2212x
2
\ue003
=
1.
d
d xt a n hx =
s e c h2x .
P r o o f.
d
d x
sin hx
c o s hx
=
(sin hx )
\ue000
c o s hx\u2212 ( c o s hx )
\ue000
sin hx
c o s h2x
=
c o s h2x\u2212sin h 2x
c o s h2x
=
1
c o s h2x
0
1
01
y
x
( c o st , s int )
x2+ y2=
1
A rea=
t
2
Search History:
Searching...
Result 00 of 00
00 results for result for
• p.
• Notes